Patterns, Determinants and Mechanisms of Unintentional Injuries among Children presenting to a Tertiary Care Emergency Department in Pakistan: A Cross-sectional Study (Journal of Fatima Jinnah Medical University, 2026)
Background: Unintentional injuries remain a contributor to childhood morbidity and mortality, with the disease burden fall-ing disproportionately on children in third-world countries. Therefore, this study aimed to determine the patterns, determi-nants and mechanisms of unintentional injuries among children presenting to the paediatric emergency of Allama Iqbal Memorial Teaching Hospital, Sialkot. Methods: An analytical cross-sectional study was conducted from 1st June to 30th November 2024 after IRB approval. Of 389 children aged 0–12 years with unintentional injuries were included by non-probability purposive sampling after taking written informed consent from parents or legal guardians. While children with chronic illness, congenital anomalies and intentional injuries were excluded. A structured questionnaire was administered. Data were analysed in SPSS version 27. Frequencies and percentages were calculated for categorical variables (gender, residence, socio-economic class), and mean ± standard deviation for continuous variables (age, monthly income). The chi-square test was used to assess associ-ations, with p-values ≤ 0.05 considered significant. Results: Of 389 children, the mean age was 6.6 ± 3.17 years and 248 (63.8%) were male children. Among determinants, inside home was the place of injury for 198 (50.9%) children, family members were caretaker at the time of injury for 382 (98.2%), and daytime was the time of injury among 256 (65.8%), while 167 (43.0%) children were under supervision. Trunk and extremities were the pattern among 248 (63.8%) children, while 256 (65.8%) had soft tissue injuries. Road traffic ac-cidents among 163 (41.9%) and falls 154 (39.6%) were the leading mechanisms. Most injuries occurred during daytime (p = 0.043) and male children were more often unsupervised at the time of injury (p = 0.021). Conclusion: Road traffic accidents and falls accounted for the majority of unintentional injuries, with male gender, daytime hours and inadequate supervision emerging as the dominant determinants. Trunk and extremities were the predominant anatomical site of injury involving mainly soft tissues as pattern of injuries.
Keywords: Wounds and injuries; accidents, children; emergency services; hospitals